A Study on Destination Image of Kerala as an Ayurvedic Health Care Destination - V T, Bindu; Swain, Sampad Kumar (Atna Journal of Tourism Studies, 2012)
Travel and health are complimentary to each other. Recently there is a demand for stress relieving holidays as people preferred to go for particular holiday destinations where their health was also looked after and where they could rejuvenate themselves. Kerala identified this need and projected itself as a healthcare destination .The Present study concentrates mainly on Kerala‟s holistic healthcare system-Ayurveda. Ayurveda plays a major role in Kerala‟s round the year tourism. The study is based on the fact that the growth in the health tourism definitely provides sustainable benefits to the Kerala tourism market. Destination image is generally considered as an important attribute in successful destination marketing. This paper aims to identify various destination features which contribute to build a positive destination image about Kerala as a healthcare destination and to understand the relationship between tourist perception and satisfaction. The study explores the destination image enhancement opportunities that exist between the tourist preferences and satisfaction in the desired healthcare service delivery.